If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -7x = 14 + -9x Solving 2 + -7x = 14 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 2 + -7x + 9x = 14 + -9x + 9x Combine like terms: -7x + 9x = 2x 2 + 2x = 14 + -9x + 9x Combine like terms: -9x + 9x = 0 2 + 2x = 14 + 0 2 + 2x = 14 Add '-2' to each side of the equation. 2 + -2 + 2x = 14 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 14 + -2 2x = 14 + -2 Combine like terms: 14 + -2 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 0=5x^2-11x+2 | | 4k-9=7k | | 30*5=x | | a^4+a^3-9a^2-9a= | | h/2x2/h | | 5r-6=1r+3 | | z=4x-4 | | 0=7h^2+10h+3 | | 7/5x | | 5x+47=-1-3x | | 2x+3x+5=50 | | a+54=180-2a | | 4k-9=7k | | 7-2x=2-4 | | (x^-2/4x^-6)^-2 | | 3x-9/40 | | 1-4k-2=-8k | | 7+-8c-48= | | 7(2x-10)-(5-7x)= | | h1/3-4=13 | | 16m^4-25m^2+9= | | 30/4.10 | | 5x+21=6x | | 4x+20=22x-12 | | 50x-5+6x+128+35x+60x=540 | | 56(56-20/4) | | t=(3x+4)(2x-5) | | 2x-3-5= | | x^8+x^4-2= | | 2-5(a-1)=9+a | | 2x-6=5-3 | | a^2x^2+b^2y^2-b^2x^2-a^2y^2= |